101 more ways to make training active - Biech, Elaine (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Liven up training with new, dynamic strategies for active participation 101 More Ways to Make Training Active brings together a rich, comprehensive collection of training strategies and activities into one easy source. Designed for quick navigation, this useful guide is packed with classroom-ready ideas and twenty "how-to" lists to enliven any learning situation, helping you better engage their trainees and encourage active participation. These techniques are applicable to almost any topic and learning objective, and provide guidance on every aspect of Active Training design and delivery. Each strategy includes recommendations for length of time, number of participants, and other conditional factors, plus a case study that illustrates the strategy in action. Coverage includes topics like communication, change management, coaching, feedback, conflict, diversity, customer service, and more, providing a complete reference for facilitating active training sessions. Active Training requires the participants to do most of the worK.T.hey use their brains, and apply what they've learned. The environment is fast-paced, fun, supportive, and personally engaging, and encourages participants to figure things out for themselves. This book contains specific, practical strategies for bringing this environment to any training session. -Learn new strategies for stimulating active discussion -Inspire creativity, innovation, and collaboration -Teach better decision making, leadership, and self-management -Make lectures active to encourage more participation Active training makes training sessions more enjoyable, and as participants invest themselves more heavily into the material, outcomes begin to improve dramatically. This dynamic atmosphere doesn't happen by accident; the activities and the course itself must be designed and delivered in a way that encourages active participation. In 101 More Ways to Make Training Active, you get a toolkit of creative, challenging, and fun ways to make it happen.
200 Tips to Make Training Active and Learning Successful -- Open Every Session Actively -- Delivering active learning.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Active learning; Training; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; Active learning; Training; Electronic books; Electronic books